Clinical Practice Guidelines of Traditional Chinese Medicine Rehabilitation for Idiopathic Scoliosis in Children and Adolescents - LI Li; YU Shaohong; ZHOU Xia; WANG Mingyue; YU Juan; WANG Shengchun; LI Nianhu; LIU Yuanfeng; CHANG Yulin; CHENG Yiran (康复学报)
Idiopathic scoliosis in children and adolescents refers to the development of unexplained scoliosis during childhood and adolescence. Chinese medicine rehabilitation is one of the effective methods to prevent its occurrence and improve clinical symptoms. In order to standardize the diagnosis and treatment of scoliosis in children and adolescents in China, to raise the attention to scoliosis in children and adolescents in society, and to ensure the standardization of Chinese medicine rehabilitation diagnosis and treatment, the expert group wrote this guideline based on the concept and method of evidence-based medicine, combined with evidence from expert discussion and clinical evaluation, and in accordance with the reporting rules of clinical treatment guidelines. This guideline covered and standardized the technical scope, normative references, terms and definitions (Cobb angle, idiopathic scoliosis, functional scoliosis, forward bending test, trunk rotation angle, weak link, core muscle strengthening, and Du-moxibustion), clinical diagnosis (clinical symptoms, clinical assessment, and imaging), TCM pattern differentiation, rehabilitation treatment [TCM rehabilitation treatment (oral administration of Chinese medicine, massage therapy, moxibustion, acupuncture therapy, acupotomy therapy, sling exercise training and traditional Chinese exercrises), modern rehabilitation therapy (physical agent modalities, exercise therapy, brace therapy and psychotherapy), prevention and management], and efficacy evaluation. This guideline can provide standardized diagnosis and treatment procedures for Chinese medicine practitioners and rehabilitation therapists in implementing Chinese medicine rehabilitation treatment of idiopathic scoliosis in children and adolescents in various rehabilitation institutions at all levels in China, the departments of rehabilitation or pediatrics in other Chinese medicine hospitals or general hospitals and provide a reliable evidence reference for clinical decision-making practice, with good clinical applicability, safety and effectiveness.